Veillonella seminalis sp. nov., a novel anaerobic Gram-stain-negative coccus from human clinical samples, and emended description of the genus Veillonella - Aujoulat, Fabien; Bouvet, Philippe; Jumas-Bilak, Estelle; Jean-Pierre, Hélène; Marchandin, Hélène (International journal of systematic and evolutionary microbiology, 2014)
Ten isolates of unknown, Gram-stain-negative, anaerobic cocci were recovered from human clinical samples, mainly from semen. On the basis of their phenotypic features, including morphology, main metabolic end products, gas production, nitrate reduction and decarboxylation of succinate, the strains were identified as members of the genus Veillonella. Multi-locus sequence analysis and corresponding phylogenies were based on 16S rRNA, dnaK and rpoB genes, and on the newly proposed gltA gene. The strains shared high levels of genetic sequence similarity and were related most closely to Veillonella ratti. The strains could not be differentiated from V. ratti on the basis of 16S rRNA gene sequence analysis while gltA, rpoB and dnaK gene sequences showed 85.1, 93.5 and 90.2 % similarity with those of the type strain of V. ratti, respectively. Phylogenetic analyses revealed that the isolates formed a robust clade in the V. ratti–Veillonella criceti–Veillonella magna subgroup of the genus Veillonella. As observed for V. criceti, the isolates were able to ferment fructose. In contrast to other members of the genus Veillonella, the 10 strains were not able to metabolize lactate. Cellular fatty acid composition was consistent with that of other species of the genus Veillonella. From these data, the 10 isolates are considered to belong to a novel species in the genus Veillonella, for which the name Veillonella seminalis sp. nov. is proposed. The type strain is ADV 4313.2T ( = CIP 107810T = LMG 28162T). Veillonella strain ACS-216-V-Col6b subjected to whole genome sequencing as part as the Human Microbiome Project is another representative of V. seminalis sp. nov. An emended description of the genus Veillonella is also proposed.